A dyadic perspective on aggressive behavior between friends. Issue 2 (26th November 2020) - Andrews, Naomi C. Z.; Hanish, Laura D.; Pepler, Debra J.
Abstract: Youth are sometimes victimized by their friends, but we know little about the nature of these relationships. Taking a dyadic approach, we studied relationships characterized by both friendship and aggression. Participants (952 middle schoolers; 50% female; 44% Latinx) nominated friends and aggressive perpetrators and victims. Using two analytic samples of friend dyads ( N = 6971) and aggressive dyads ( N = 4662), results indicated that aggression by a friend was somewhat common. Compared with friend dyads without aggression, aggressive friend dyads were stronger (i.e., reciprocal) and longer lasting, though victimized youth were less satisfied with the friendship. Aggressive dyads who were friends more often had reciprocal aggression than aggressive dyads who were not friends. Results provide insight into the dynamics of aggression in close peer relationships.